PENTINGNYA MORALITAS BAGI KEHIDUPAN ORANG KRISTEN BERDASARKAN ULANGAN 24 :14-15 - Irafanda Salauwe (Sabda: Jurnal Teologi Kristen, 2022)
The importance of Morality for Christian life. In this article, the author talks about how to be a Christian with good morals, love others, and of course have an impact on the lives of the surrounding community. In this case, the author invites Christians not only to care about the people around them but how Christians care, embrace marginalized people who have nothing. Apart from that, as Christians, we must play an important role in the sense that we are to be examples for our neighbors. This study of Deuteronomy discusses how a Christian can love his fellow human beings. In this article, the author also uses the legal interpretation method. The research result of this article is a Christian who loves others and obeys God. Which of course is reflected in the life of these Christians. For this reason, every Christian must obey and follow the commands that God has given to His people. Because God sees the obedience of each person in maintaining his covenant with God.